Reviews of Science for Science Librarians: The National Weight Control Registry - 25 Years of Compiling Strategies Used by Long Term Weight Loss Maintainers. Issue 2 (3rd April 2019) - Stankus, Tony
ABSTRACT: Established in 1994, the National Weight Control Registry (NWCR) is a repository for the completed questionnaires and medical records of more than 10, 000 individuals distinguished by their having intentionally lost thirty of more pounds and maintaining that loss for at least a year. As one means of assessing the impact of the NWCR, the extent to which articles highlighted on its website are cited in the Web of Science Core Collection is reported, along with the journals and author affiliations of those referencing these works. Well over a thousand papers originating from a distinguished roster of universities with dedicated centers for research and treatment in nutrition and obesity, published in the journals most important to experts in these areas, clearly demonstrate both the legacy and ongoing importance of the NWCR.